Management Of Acceleration Program In The Special Intelligent Children Service at State‐Owned Elementary School Cemara Dua Surakarta - Suyanto, Suyanto (2012)
This study has four objectives. The first is to describe the characteristics of Acceleration program curriculum in service for special intelligent children at State‐Owned Elementary School Cemara dua Surakarta. The second objective is to elaborate the instructional characteristics of the Acceleration program in service for special intelligent children at State‐Owned Elementary School Cemara dua Surakarta. The third is to describe the infrastructure characteristics of Acceleration program in service for special intelligent children at State‐Owned Elementary School Cemara Dua Surakarta. And the last objective is to describe the funding characteristics of Acceleration program in service for special intelligent children at State‐Owned Elementary School Cemara Dua Surakarta It is a qualitative research. The informants of this study include the principal, the vice principal of curriculum affair, the vice principal of facilities and infrastructure affair, teachers, and students. Data collection method uses in‐ depth interview, observation, and documentation. Data analysis uses an analysis technique arranged in site. Datavalidity uses triangulation. The findings suggest that: (1) The curriculum used in the Acceleration program is the national education standard, in which in its application the allocation of time is becoming shorter and developed based on the principles centered on the potential, development need and interest of learners, as well as relevant to the need of life. This curriculum is developed by the school, involving experts from the college environment, and guided by the standards of competency and content as well as curriculum guidelines made by the National Education Standard Board. The curriculumis developed in a differential way covering four dimensions; (2) The Acceleration learning program is done in two classes i.e. class IV and V.Learning followed by students who pass the selection, and it is done by the package system in accordance with the curriculum. The time is faster (acceleration) through an open system, structured assignment, and unstructured activities independently. Learning activities directed at the realization of mastery learning process with a strategy aimed to stimulate students to be active and creative; (3) The Acceleration infrastructure program is managed in an integrated manner by the vice principal of infrastructure area, which also manages regular class infrastructure and the pioneering of international standard school. School infrastructure management system using the standard ISO 90 001: 2008; Financing of the Acceleration program is from three sources‐School Operational Assistance based on procedures, CIBI scholarships with a proposal to the province, and parents.